AHWALNOTE ISLAMIC APP UI/UX IMPROVEMENTS WITH JAKOB'S TEN USABILITY HEURISTICS AT INDI TECHNOLOGY - Amrullah, Fadlan; Yushendri, Jefri; Tju, Teja Endra Eng (Universitas Pelita Harapan, 2023)
AhwalNote is an Islamic mobile app to help depressed people avoid suicide. There is a desire from INDI Technology to improve and add AhwalNote features so that it is assisted in the development of the application with Jakob's Ten Usability Heuristics method. The activity is divided into three stages: the Preparation Stage with observation and interview methods; the Socialization stage with presentation, question and answer, discussion, and practice methods; and the Evaluation Stage is the assessment stage of the development results using the Severity Ratings method. The results of these activities are measured by comparing the evaluation results between the old and the new version of AhwalNote shown with the Severity Ratings value. There are some improvements in the quality of AhwalNote's UI/UX or Usability as a result of the development team of INDI Technology. Furthermore, Jakob's Ten Usability Heuristics method can be applied at the time of development of an application so that the final result before it is released is not too far from the standard usability.